Congenital heart disease among 815,569 children born between 1980 and 1990 and their 15-year survival: a prospective Bohemia survival study - Samánek, M; Vorísková, M (Pediatric cardiology, 1999)
The objective of this study was to ascertain the prevalence and survival rate of children born with a heart defect. A total of 816, 569 children live-born between 1980 and 1990 in Bohemia (52,478 km(2), population 6.314 million, western Czech Republic) were followed up and those with suspected heart disease referred to a center. Echocardiography was done in all of them. All dead children were autopsied. Congenital heart disease was found in 5030 of 816, 569 children (6.16 per 1000 live births). The most frequent conditions were ventricular septal defect (41.59%), atrial septal defect (8.67%), aortic (7.77%) and pulmonary (5.81%) stenoses, transposition of the great arteries (5.39%), coarctation of the aorta (5.29%) and persistent ductus arteriosus (5.07%). The first week was survived by 92.46%, the first month by 89.14%, 6 months by 82.42%, and the first year of life by 80.02%, and 77.11% (95% CI 75. 91-78.31%) survived to age 15 years. The best prognosis was found in pulmonary stenosis (15-year survival 95.55%), atrial septal defect (92.04%), persistent ductus arteriosus (90.59%), ventricular septal defect (89.37%) and aortic stenosis (88.39%). The worst results were attained in hypoplastic left heart, truncus arteriosus and pulmonary atresia with intact ventricular septum. In conclusion, the prevalence of congenital heart disease was 6.16 per 1000 live births; 77.11% of patients survived to age 15 years.
Keywords: novorozenec; Infant, Newborn; surveillance populace; Humans; prevalence; pojišťovací analýza; Prospective Studies; lidé; Actuarial Analysis; vrozené srdeční vady; Survival Rate; prognóza; Czech Republic; Prevalence; Population Surveillance; míra přežití; Česká republika; prospektivní studie; Prognosis; Heart Defects, Congenital